Phenomenological study of thermal aging effects on intermetallic growth mechanisms and shear strength behavior of wafer level solder bumps - Amistoso, Jose Omar S.
The effect of wafer level solder bump size on solder bump strength and intermetallic growth as a function of time, at different storage temperatures is studies, using solder bumps of two different heights :95 um (SB95) and 142 um (SB142). Smaller solder bumps (SB95) lead to a faster decrease in bump shear strength. Increasing aging temperature and time brings about an increase in the final fracture area of the solder, and It is observed that the smaller solder bump (SB95) exhibits a faster rate of increase in final fracture area, than the bigger bump. A linear decrease of solder bump strength with intermetallic thickness is established for the systems studied.